A Review of Low Temperature NH3-SCR for Removal of NOx - Devaiah Damma (Catalysts, 2019)
The importance of the low-temperature selective catalytic reduction (LT-SCR) of NOx by NH3 is increasing due to the recent severe pollution regulations being imposed around the world. Supported and mixed transition metal oxides have been widely investigated for LT-SCR technology. However, these catalytic materials have some drawbacks, especially in terms of catalyst poisoning by H2O or/and SO2. Hence, the development of catalysts for the LT-SCR process is still under active investigation throughout seeking better performance. Extensive research efforts have been made to develop new advanced materials for this technology. This article critically reviews the recent research progress on supported transition and mixed transition metal oxide catalysts for the LT-SCR reaction. The review covered the description of the influence of operating conditions and promoters on the LT-SCR performance. The reaction mechanism, reaction intermediates, and active sites are also discussed in detail using isotopic labelling and in situ FT-IR studies.